Early life stages of fishes in plant communities in a cove at Aliceville Lake, Alabama-Mississippi, USA - Ferrer Montaño, Orlando José; Dibble, Eric (Ciencia)
Aquatic plants in backwater areas play, in many instances, important roles in structuring freshwater fish assemblages. This study examined the overall importance for fishes of vegetated backwater habitats in a cove at Aliceville Lake, an impoundment of the Tennessee-Tombigbee Waterway. An inventory of adult fishes compiled from earlier reports was made and compared it with early life stages of fishes collected with light traps. The overall efficiency of light traps for collecting early life stages of fishes was also tested. It was expected that abundance and species richness of young fishes collected reflected the overall abundance and species richness reported in the literature. A total of 1,778 fishes (1,388 early life stages, 78%, and 390 juveniles, 22%) representing 12 genera and 10 families was collected. These 10 families represented 62.5% of the families previously reported having adults in Aliceville Lake. Experimental tests confirmed that the light trap is efficient in attracting fishes as long as they are present in its area of influence. Even though the cove studied contained diverse macrophyte beds that lead to highly variable habitat use by young fishes, the obtained results confirmed that it was not as strongly used as spawning ground as it would be predict based on previous reports. Factors influencing this variability in macrophyte beds still remain unknown. Fishes at Aliceville Lake may respond to habitat complexity at scales other than those considered in this study and along habitat structure other than macrophytes. Although this study documents important use of vegetated backwaters at Aliceville Lake, further investigation is necessary to better understand the complex relation between early life stages of fishes and aquatic plants. Identification of these factors and knowledge of their mechanisms would facilitate better management of these ecologically important ecosystems.